The production of child health in Kenya: a structural model of birth weight - Germano Mwabu (Yale University, Economic Growth Center, 2008)
The paper investigates birth weight and its correlates in Kenya using nationally representative data collected by the government in the early 1990s. I find that immunization of the mother against tetanus during pregnancy is strongly associated with improvements in birth weight. Other factors significantly correlated with birth weight include age of the mother at first birth and birth orders of siblings. It is further found that birth weight is positively associated with mother's age at first birth and with higher birth orders, with the first born child being substantially lighter than subsequent children. Newborn infants are heavier in urban than in rural areas and females are born lighter than males. There is evidence suggesting that a baby born at the clinic is heavier than a newborn baby drawn randomly from the general population.
Keywords: C31; C34; I11; I12; J13; 330; Health care demand; immunization; health production; birth weight; control function approach; weak instruments; multiple endogenous variables; Kinder; Gesundheit; Gesundheitsversorgung; Kenia